Factor influencing the production and properties of extracellur protease from Streptomyces bikiniensis - Wahid, SUH; Ferdouse, J; Anwar, MN (Chittagong University Journal of Biological Sciences, 2013)
The actinomycete Streptomyces bikiniensis collected from laboratory stock culture, Department of Microbiology, University of Chittagong was found to be a protease producer. Effect of various culture conditions for the production of protease from S. bikiniensis and its properties were determined in the present study. The organism showed maximum protease yield at temperature 37°C with an initial culture, pH 7.0 after 4 days of incubation period under stationary condition. The crude enzyme preparation exhibited highest activity at substrate (casein) concentration of 1.0% with a reaction time of 75 min, at 40°C and pH 6.0. EDTA was found to a potent inhibitor of protease of the isolate while, 1,2- epoxy-3-(P-nitrophenoxy) propane exhibited low inhibitory effect on the enzyme activity. The enzyme was partially purified by precipitation method using ammonium sulfate fractionation and the maximum amount of the enzyme was precipitated at 60% saturation. DOI: http://dx.doi.org/10.3329/cujbs.v4i1.13399 The Chittagong Univ. J. B. Sci.,Vol. 4(1&2):153-163, 2009